Functional Peptides Encoded by Long Non-Coding RNAs in Gastrointestinal Cancer - Chen, Yao; Long, Weili; Yang, Liqiong; Zhao, Yueshui; Wu, Xu; Li, Mingxing; Du, Fukuan; Chen, Yu; Yang, Zhihui; Wen, Qinglian; Yi, Tao; Xiao, Zhangang; et al. (Frontiers in Oncology, 2021)
Gastrointestinal cancer is by far the most common malignancy and the most common cause of cancer-related deaths worldwide. Recent studies have shown that long non-coding RNAs (lncRNAs) play an important role in the epigenetic regulation of cancer cells and regulate tumor progression by affecting chromatin modifications, gene transcription, translation, and sponge to miRNAs. In particular, lncRNA has recently been found to possess open reading frame (ORF), which can encode functional small peptides or proteins. These peptides interact with its targets to regulate transcription or the signal axis, thus promoting or inhibiting the occurrence and development of tumors. In this review, we summarize the involvement of lncRNAs and the function of lncRNAs encoded small peptides in gastrointestinal cancer.